2014
DOI: 10.4172/2161-0703.1000170
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Imipenem-Resistant Genes in Acinetobacter baumannii Isolated from Baghdad Hospitals

Abstract: Imipenem-resistant Acinetobacter baumannii (IRAB) represents one of the important causing agents of nosocomial infections especially in immunocompromised and Intensive Care Units (ICUs) patients. The aim of this work was to identify the Imipenem-Resistant genes in Acinetobacter baumannii isolated from Baghdad hospitals. Among 128 A. baumannii isolates, 67 isolates (58.26%) were resistant to imipenem and meropenem. Four genes for imipenem resistance (blaOXA-23 like, blaOXA-24 like, blaOXA-51like and blaOXA-58 l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
(14 reference statements)
3
7
0
Order By: Relevance
“…The results of gel electrophoresis for PCR product by using specific primers for this genes showed that one isolate were positive for this genes as shown in Figure (1,2,3) , While 43 /45 (95.5%) of isolates were Negative for this =0= genes. These results nearly agrees with many local studies such as study of Hussein (2013) who referred to the low prevalence of OXA gene, another study of the most middle east countries also showed the low prevalence of this genes in isolates of P.aeruginosa . In addition to that, some isolates were have more than one genes of ESBLs, These results nearly agrees with many local studies such as A study in Ilam (Iran) noticed that among (70) isolates of E.coli collected from hospitalized patients, two isolates (85%) were positive for blaCIT (10).…”
Section: Biofilm Production By P Aeruginosasupporting
confidence: 90%
See 1 more Smart Citation
“…The results of gel electrophoresis for PCR product by using specific primers for this genes showed that one isolate were positive for this genes as shown in Figure (1,2,3) , While 43 /45 (95.5%) of isolates were Negative for this =0= genes. These results nearly agrees with many local studies such as study of Hussein (2013) who referred to the low prevalence of OXA gene, another study of the most middle east countries also showed the low prevalence of this genes in isolates of P.aeruginosa . In addition to that, some isolates were have more than one genes of ESBLs, These results nearly agrees with many local studies such as A study in Ilam (Iran) noticed that among (70) isolates of E.coli collected from hospitalized patients, two isolates (85%) were positive for blaCIT (10).…”
Section: Biofilm Production By P Aeruginosasupporting
confidence: 90%
“…this difference in results may be due to the type of media used or the laboratory conditions that accompanied the detection of biofilm formation among our results and disagrees results in some previous study. From the other hand, The variation in the ability of isolates to form biofilm back to association of production with its ability to produce ß-Lactamase, where the isolates produced of multiple types of enzyme were produce a strong biofilm, compared with isolates that produce one type of enzyme, while the isolates that do not produce this enzyme do not form biofilm (9). Molecular Detection of Some Genes Responsible for ESBL In Pseudomonas aeruginosa Isolates: ESBLs genes OXA-10, OXA-4 and VEB-1 was screened by PCR technique for the forty-five isolates.…”
Section: Biofilm Production By P Aeruginosamentioning
confidence: 99%
“…The bla OXA-51 -like genes were reported to be highly specific for the identification of A. baumannii at the species level (9) . PCR product illustrate the presence of blaOXA-51-like genes in all 15 (100%) A. baumannii clinical isolate close to Nadeema et al (10) . figure 1.…”
Section: Molecular Detection Of Bla Oxa-51 In a Buammanii By Traditio...mentioning
confidence: 77%
“…Biochemical tests were carried out, such as S. epidermidis gram-positive bacteria, P. mirabilis, and A. baumannii, which appeared gram-negative bacteria. In terms of the ability of gram-negative bacteria P. mirabilis and A. baumannii to ferment lactose, they were not fermentable when grew on macConkey agar medium, and there was no hemolysis of these bacterial isolates when they grew on the medium of blood agar, and S .epidermidis bacteria it was not fermented mannitol when grown on mannitol salt agar medium, other tests showed negative results for both coagulase test and oxidase test, whereas positive result for Catalase test, growth test at 44 temperature was positive for A. baumannii bacteria and motility test was positive for P. mirabilis bacteria [37,38] as shown in Table (1).…”
Section: Biochemical Testsmentioning
confidence: 94%